Ras mediates Src but not epidermal growth factor-receptor tyrosine kinase signaling pathways in GH4 neuroendocrine cells. - Pickett, C A (1994)
p21Ras has been implicated as a critical signaling component in mediating the effects of many growth factor receptor/tyrosine kinases on cell growth and differentiation. However, the precise functional role of Ras in establishing a cell-specific transcriptional response to a ubiquitous growth factor remains unclear. We have utilized a transient cotransfection model system in epidermal growth factor (EGF)-responsive cultured GH4 rat pituitary neuroendocrine cells to investigate the role of Ras in coupling EGF receptor (EGF-R) and v-Src tyrosine kinase signals to the activation of a cell-specific promoter for the rat (r) prolactin (PRL) gene. A significant dose- and time-dependent EGF stimulation of the transfected rPRL promoter was obtained. A similar degree of activation of the rPRL promoter was obtained by cotransfection of a plasmid encoding v-Src. Cotransfection of a construct encoding the dominant-negative Ras, N17Ras, produced almost complete inhibition of v-Src-induced rPRL promoter activity, while EGF-stimulated rPRL promoter activity was unaffected. Similarly, EGF activation of a c-Fos promoter was unaffected by N17Ras, while v-Src activation was blocked. Hence, using transcription regulation as a functional assay, we show that Ras is not required for the EGF-mediated control of the rPRL and c-Fos promoters, whereas Ras is critical in mediating the v-Src effects to these two promoters. These observations emphasize that, despite current biochemical data linking the EGF-R and Ras pathways, the functional significance of such an interaction should be analyzed in a biologically relevant manner and may differ as a function of cell type.